Exploring Consumer Awareness of Health and Environmental Implications of Lead Toxicity in Household Paints - Aigbogun, Osaro; Ghazali, Z.; Xing, M.; Fawehinmi, O.; Abdullahi, M.; Uwakina, J. (2023)
Despite the dangers of lead toxicity to population and environmental health, studies have revealed proliferation of above threshold concentration of lead in household paints in several locations. This paper presents the findings from an exploratory study in Peninsular Malaysia on the level of public awareness of the adverse effects of exposure to lead-based household paints. Primary quantitative data were gathered in a cross-sectional questionnaire survey on a conveniently recruited population residing in 5 Malaysian cities. The survey generated 657 valid responses, which were subjected to statistical analysis. The results show that the survey participants are highly aware of lead usage in household paints. Furthermore, their awareness about the health and environmental implications were also high, and a significant difference was observed in association with specific demographic characteristics such as gender, age and educational level. These findings highlight that majority of the respondents are aware of the health and environmental implications of lead-based household paints. However, this result does not reflect the production quality of the household-based paint in Malaysia, which studies have shown to be above threshold concentrations. This exploratory study creates room for future studies to undertake further investigations among consumers and organizations.